ENZIM LIPOPROTEIN LIPASE SUATU ALTERNATIF PEMERIKSAAN GANGGUAN METABOLISME LEMAK PADA PENDERITA DM TIPE 2 IN VITRO - Handayani, Dian; Soeadmadji, Djoko W.; Widodo, M. Aris; Am, Aulani’ (Jurnal Kedokteran Brawijaya, 2003)
ABSTRACT The biggest population of Diabetes Mellitus is type 2 diabetes. Dyslipidemia is frequently found in type 2 diabetic patients, which is characterized by increased TG plasma levels and decreased HDL. Increased TG levels may be due to LPL activity disturbance, which then  lead to impaired lipoprotein metabolism, such as decreased hydrolyzing TGs in VLDL and Chylomicron. LPL is an enzyme which activities are influenced by several factors such as temperature, pH, incubation period, and substrate concentration. LPL attached to vascular endothelium, and can be removed from it by giving heparin intravenous. Heparin acts as lipotropic agent which promote plasma lipid transfer to lipid deposit by secreting lipolitic enzyme such as LPL. After giving information  about the objective of this study on the possible site effect of the blood obtaining technique, the patient was asked  to give her voluntary consent. Heparin IV 60 IU/Kg BB was given 15 minute before blood sample was drawn. Obtain from aid type 2 diabetes individual and aid from non diabetic control subject. To determine optimal LPL action pH variations (6, 6.4, 6.8 and 7), temperature  (30, 32, 35 and 37)oC,